Consecutive days of prolonged tennis match play: performance, physical, and perceptual responses in trained players - Gescheit, D. T.; Cormack, S. J.; Reid, M.; Duffield, R. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To determine how consecutive days of prolonged tennis match play affect performance, physiological, and perceptual responses. Methods: Seven well-trained male tennis players completed 4-h tennis matches on 4 consecutive days. Pre- and postmatch measures involved tennis-specific (serve speed and accuracy), physical (20-m sprint, countermovement jump [CMJ], shoulder-rotation maximal voluntary contraction, isometric midthigh pull), perceptual (Training Distress Scale, soreness), and physiological (creatine kinase [CK]) responses. Activity profile was assessed by heart rate, 3D load (accumulated accelerations measured by triaxial accelerometers), and rating of perceived exertion (RPE). Statistical analysis compared within- and between-days values. Changes (± 90% confidence interval [CI]) =75% likely to exceed the smallest important effect size (0.2) were considered practically important. Results: 3D load reduced on days 2 to 4 (mean effect size ± 90% CI -1.46 ± 0.40) and effective playing time reduced on days 3 to 4 (-0.37 ± 0.51) compared with day 1. RPE did not differ and total points played only declined on day 3 (-0.38 ± 1.02). Postmatch 20-m sprint (0.79 ± 0.77) and prematch CMJ (-0.43 ± 0.27) performance declined on days 2 to 4 compared with prematch day 1. Although serve velocity was maintained, compromised postmatch serve accuracy was evident compared with prematch day 1 (0.52 ± 0.58). CK increased each day, as did ratings of muscle soreness and fatigue. Conclusions: Players reduced external physical loads, through declines in movement, over 4 consecutive days of prolonged competitive tennis. This may be affected by tactical changes and pacing strategies. Alongside this, impairments in sprinting and jumping ability, perceptual and biochemical markers of muscle damage, and reduced mood states may be a function of neuromuscular and perceptual fatigue.